1992
DOI: 10.1149/1.2069198
|View full text |Cite
|
Sign up to set email alerts
|

The Passivity of 304 Stainless Steel in Propylene Carbonate Solutions

Abstract: The passivation behavior of 304 stainless steel in anhydrous propylene carbonate (PC) containing 0.5M LiAsF6 or 0.5M LiC104 was studied. The air-formed film on 304SS is stable up to the oxidation potential of PC (PCox). Scratch tests show that the bared 304SS surface repassivates in the anhydrous PC solutions of either electrolyte by chemisorption of PC molecules below PCox. In PC/0.5M LiAsF6 solutions, the 304SS is not passivated at potentials above PCox. In PC/0.5M LiC104 solutions the 304SS is passive at po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This behavior is similar to that described for 304 stainless steel in anhydrous propylene carbonate. 16 Under strong anodic polarization (above 1.05 V vs Fc/Fc + ), the rise of current density is similar to that observed in transpassive dissolution in aqueous solutions, indicating that the initial passive film is dissolved, at least to some extent. Because there is no similar rise of current density on Pt, we can infer that the increase in current density exhibited on C-22 is truly due to the oxidation of the metal and not of the electrolyte or solvent.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This behavior is similar to that described for 304 stainless steel in anhydrous propylene carbonate. 16 Under strong anodic polarization (above 1.05 V vs Fc/Fc + ), the rise of current density is similar to that observed in transpassive dissolution in aqueous solutions, indicating that the initial passive film is dissolved, at least to some extent. Because there is no similar rise of current density on Pt, we can infer that the increase in current density exhibited on C-22 is truly due to the oxidation of the metal and not of the electrolyte or solvent.…”
Section: Discussionsupporting
confidence: 56%
“…Once the oxide was removed, repassivation could take place by either salt film formation or solvent adsorption, depending on the potential. 16 Of the myriad of species present in processes involving aprotic solvents, quinones deserve attention due to their redox-active behavior and their usefulness in biologic processes, as well as in the energy, pharmaceutical and chemical industries. 17 Although many studies have been dedicated to understanding the redox behavior of quinones, few studies have reported its effect on corrosion of metals.…”
mentioning
confidence: 99%
“…19 However, SS304 has been shown to passivate readily in LiClO 4 /PC electrolytes up to 4.9 V vs Li/Li + , but in LiAsF 6 /PC only up to 4.1 V vs Li/Li + . 128 A common feature of SS and Fe is that EC considerably reduces the corrosion stability. This may be because the corrosion products are more soluble in EC-based solvents.…”
Section: Metallic Alloysmentioning
confidence: 99%
“…In 1974, Heitz reviewed the state of the understanding of the corrosion of metals and alloys in organic solvents [8]. Kurger et al [9][10][11][12] observed that type 304 stainless steel readily passivated up to 4.9 V vs. Li /Li + in LiClO 4 /PC, even though the detailed passivation mechanism was not clarified.…”
Section: Introductionmentioning
confidence: 99%